Information Security Management, Education and Privacy IFIP 18th World Computer Congress TC11 19th International Information Security Workshops 22–27 August 2004 Toulouse, France - Deswarte, Yves; Cuppens, Frederic; Jajodia, Sushil; Wang, Lingyu (IFIP Advances in Information and Communication Technology, 2004)
This volume gathers the papers presented at three workshops that are embedded in the IFIP/Sec Conference in 2004, to enlighten specific topics that are currently particularly active in Security. The first one is the 10th IFIP Annual Working Conference on Information Security Management. It is organized by the IFIP WG 11. 1, which is itself dedicated to Information Security Management, i. e. , not only to the practical implementation of new security technology issued from recent research and development, but also and mostly to the improvement of security practice in all organizations, from multinational corporations to small enterprises. Methods and techniques are developed to increase personal awareness and education in security, analyze and manage risks, identify security policies, evaluate and certify products, processes and systems. Matt Warren, from Deakin University, Australia, who is the current Chair of WG 11. 1, acted as the Program Chair. The second workshop is organized by the IFIP WG 11. 8, dedicated to Information Security Education. This workshop is a follow-up of three issues of the World Conference on Information Security Education (WISE) that were also organized by WG 11. 8. The first WISE was organized by Louise Yngstrom in 1999 in Stockholm, and the next one, WISE’4, will be held in Moscow, Russia, 18-20 May 2005. This year, the workshop is aimed at developing a first draft of an international doctorate program allowing a specialization in IT Security